Mathematical modelling of livestock production systems: Application of the Texas A & M University beef cattle production model to Botswana - International Livestock Centre for Africa (International Livestock Centre for Africa, 1978)
The animal science systems group at Texas A & M University (TAMU) has developed a computer based beef cattle production model for use in tropical countries. This model can be used to predict animal and herd productivity under a variety of management regions in diverse environments. Economic analyses can then be made, based on these predictions. ILCA, therefore sponsored the application of the TAMU model in Botswana with the objectives of introducing computer-based modelling techniques to researchers and identifying where applications of modelling techniques would assist research and development activities. The first section of this report outlines the two basic systems of beef cattle production in Botswana and principal research findings. A summary of previous application of the model and a description of its essential features, including the key functional relationships it includes are presented in section two which also outlines in general terms the methodology of computer based modelling. The third chapter outlines the methods used and the values derived for its application on Tswana cattle in Botswana. Section four summarises initial studies where the results of five sets of simulation runs are presented. The discussion in this chapter focuses on the biological responses of the systems to the various interventions. An economic interpretation of selected results is presented in section five whereas section seven identifies further possible applications of the modeling methodology to the livestock production systems in Botswana.